O nekim zanimljivim rezultatima postignutim u Hrvatskoj u području kemijske teorije grafova (On Some Interesting Results Achieved in Chemical Graph Theory in Croatia) - Trinajstić, N. (Kemija u Industriji, 2006)
Some interesting results achieved in chemical graph theory in Theoretical Chemistry Group at the Rugjer Bošković Institute are briefly reviewed. In the article are discussed the use of the Sachs theorem for the construction of the characteristic polynomial of molecules, the topological resonance energy as a measure of aromaticity, isospectral molecules, the development of algorithms for the generation and enumeration of Kekulé structures, the analysis of the conjugated-circuit model and its application to fullerenes, the analysis of various graph-theoretical matrices, the development of the computational method CROMRsel for modeling molecular properties by means of descriptors, the development and application of algorithms for the enumeration of various classes of molecules and the studies of the complexity of molecules and chemical reactions. Numerous co-workers and visitors that did research in chemical graph theory in Theoretical Chemistry Group are listed.